2013
DOI: 10.1021/cs400622e
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystallography Reveals How Subtle Changes Control the Orientation of Substrate Binding in an Alkene Reductase

Abstract: Reductions of (S)-and (R)-carvone by wild-type Saccharomyces pastorianus Old Yellow Enzyme (OYE 1) and a systematic collection of Trp 116 variants revealed that, for (S)-carvone, six Trp 116 mutants displayed inverted diastereoselectivity compared to the wild-type. For example, Ile and Val showed inverted stereoselectivity, but Leu and Phe maintained the wildtype stereopreference. For (R)-carvone, only two Trp 116 mutants (Ala and Val) reduced this alkene with reversed selectivity; all other catalytically acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 43 publications
4
64
0
Order By: Relevance
“…Further, the same pattern of stereocomplementarity for the glycine/threonine and aspartate/threonine variants was observed for the reduction of 3 , allowing access to (2 S ,5 S )‐ 4 or (2 R ,5 S )‐ 4 with excellent diastereoselectivities of up to 92 or 96 % de , respectively. This is the first report of group 2 members producing (2 S ,5 S )‐ 4 and—other than OYE1 W116X variants from group 1—they represent the only other set of variants so far for this reaction . All our other new variants led to (2 R ,5 S )‐ 4 , even the hotspot position III homologues NCR W100I and TsER A102I.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Further, the same pattern of stereocomplementarity for the glycine/threonine and aspartate/threonine variants was observed for the reduction of 3 , allowing access to (2 S ,5 S )‐ 4 or (2 R ,5 S )‐ 4 with excellent diastereoselectivities of up to 92 or 96 % de , respectively. This is the first report of group 2 members producing (2 S ,5 S )‐ 4 and—other than OYE1 W116X variants from group 1—they represent the only other set of variants so far for this reaction . All our other new variants led to (2 R ,5 S )‐ 4 , even the hotspot position III homologues NCR W100I and TsER A102I.…”
Section: Resultsmentioning
confidence: 56%
“…In addition to the above studies, a few single‐residue saturation mutagenesis, rational design or directed evolution studies that allow extraction of engineered residues exist. Taken together, several hotspot positions have been identified, and positions I, II, and III (Figure ) in particular were found to control facial selectivity, activity and substrate scope in OYE1, OYE2.6, PETNR, KYE and YqjM …”
Section: Introductionmentioning
confidence: 99%
“…However, the group of Pietruszka showed that the stereoselectivity of an uncharacterised OYE could not be predicted solely based on the primary sequence pattern of the surface loop β2 [126]. Stereoselectivity was also investigated by the group of Stewart, who determined how subtle changes in the residues control the orientation of substrate binding in OYEs [127,128], and showed that mutations can lead to inverted enantioselectivity [129,130]. The stereochemical outcome was influenced by mutagenesis of Trp116 in OYE1.…”
Section: Classification Of Oyes With Respect To Substratesmentioning
confidence: 99%
“…Thus, combining ene‐reductases with ketoreductases was performed to create dihydrocarveol stereoisomers. The biocatalytic reduction of activated C=C bond of carvone ( 1 ) to give dihydrocarvone ( 3 ) has been well studied by several ene‐reductases ,,,. For example, (1 R ,4 R )‐ 3 and (1 R ,4 S )‐ 3 could be obtained through asymmetric reduction of corresponding (4 R )‐ 1 and (4 S )‐ 1 by various ene‐reductases, such as OYE1,, PETNR, and so on .…”
Section: Resultsmentioning
confidence: 99%
“…The biocatalytic reduction of activated C=C bond of carvone ( 1 ) to give dihydrocarvone ( 3 ) has been well studied by several ene‐reductases ,,,. For example, (1 R ,4 R )‐ 3 and (1 R ,4 S )‐ 3 could be obtained through asymmetric reduction of corresponding (4 R )‐ 1 and (4 S )‐ 1 by various ene‐reductases, such as OYE1,, PETNR, and so on . However, only a few ene‐reductase variants, such as OYEW116A/V and TsER C25G/I67T, displayed switched stereoselectivity to yield dihydrocarvone with S configuration at C‐1 position.…”
Section: Resultsmentioning
confidence: 99%